142k views
4 votes
What’s the answer to this math problem ?

What’s the answer to this math problem ?-example-1
User RobotRock
by
5.4k points

2 Answers

1 vote

{10}^(2) - {6}^(2) = {(the \: entire \: triangles \: height}^(2) \\ = 100 - 36 \\ = 64 = {(the \: entire \: triangles \: height}^(2) \\ this \: means \: the \: entire \: triangles \: height \: = 8 \\ \\ now \: {17}^(2) - {8}^(2) \\ = {(the \: length \: of \: the \: base \: of \: the \: left \: triangle)}^(2) \\ \\ so \: {17}^(2) - {8}^(2) = 225 \\ = {(length \: of \: the \: base \: of \: the \: left \: triangle)}^(2) so \\ the \: length \: of \: the \: base \: of \: the \: left \: triangle \: = 15 \\ \\ the \: base \: of \: the \: triangle \: is \: 15 + 6 = 21 \: and \: its \: height \: is \: 8 \\ \\ the \: triangles \: are \: is \: (1)/(2) * base \: * height \\ = (1)/(2) * 21 * 8 = 84
User Joshua Barker
by
5.5k points
3 votes
Answer : 30 units squared

Multiply 6 by 10, then divide by 2.



User Tanel
by
5.9k points